Formação dos profissionais da limpeza na perspectiva freireana: a (in)visibilidade dos educadores não docentes - Rodrigues, Vanessa Barbato (2017)
The work done in schools does not depend on teaching professionals only. There are other people, also indispensable, in the institutions daily routine, like cleaning and kitchen staff, employees that, generally, are outsourced. However, in most part of the schools, those employees are unrelated to discussions and decisions that subsidize the building of the Political-pedagogic Project, showing a subaltern posture against managers and other members of the school community. Starting from that reality, the present research studies which elements from Paulo Freire´s pedagogy can contribute to the building of an investigative and a formative way process, that enables to the non-teaching professionals assume their roles as educators in the school environment, getting out of the condition of mere support to the educational process. The formative and analytical practice described on this paper is based on the principles of the theme investigation, coherent methodology with the perspective of a problematizing and emancipatory education. The formation work, involving outsourced employees that act in a municipal public school, located in São Paulo city, was developed by me, a researcher and principal of the school, along twelve meetings, all happened during 2015. The analysis of the results of the research shows that the person formation contributes a lot to the comprehension and superaction of an inhuman reality experienced by those characters in daily school routine: the invisibility